Epidemiologia dos acidentes de trânsito com vítimas na cidade de Uberlândia (MG) - Câmara, Magnus Rômulo (2007)
The search for measures which contribute to the reduction in morbid-mortality caused by traffic accidents has to pass through the identification of their causes. With the objective of understanding the epidemic factors of traffic accidents with victims assisted by the rescue units from the Military Firemen Department of the Fifth Battalion in Uberlândia, Minas Gerais, Brazil, a study has been made addressing the factors relating to the human being, means of transport, transport routs and assistance rendered, during the period from November 2003 to October 2004. It was, then, that one of the researchers accompanying in a prospective manner one of the rescue units during its pre-hospital care. In the studied period were analysed 296 traffic accidents with 397 victims, among the results obtained it is noteworthy that 284 (71,5%) are victims with ages varying between 15 and 39 years, it have been participation equal in the male 284 (71,5%); 267 (67,2%) were drivers of some means of transport or other; 141 (39,8%) of the victims drivers should have been using obligatory evaluated safety equipment, but were not; 28 (68,3%) of the pedestrians adopted risky conduct when crossing the road in forbidden places; 149 (50,3%) of the traffic accidents were collisions; ¼ (26,3%) involved in running down pedestrians left the scene; 82 (27,7%) of the traffic accidents occur close to the victim's home; 133 (44,9%) of the traffic accidents occur between 14:00 and 20:00 and 133 (35,1%) of the traffic accidents occur at the weekends; 247 (62,2%) of the victims were directed to secondary complexity emergency hospitals. It can be conclude that the victims are young persons adults in the 15 to 39 age group and in their majority driving motorized vehicles. When driving, more than a third do not use safety equipment and the pedestrians usually adopted conduct risky to life crossing or walking in forbidden places on the road. Collisions were the most common accidents. More than a fourth of the drivers involved in the traffic accidents leave the scene of the accident when a pedestrian is run over. A fourth of the traffic accidents occur close to the victim's home. The traffic accidents intensify during the time at the end of the afternoon and beginning of evening and at weekends. the victims are generally directed to medical center of secondary complexity.